Electronic properties of 4,4',5,5'-tetramethyl-2,2'-biphosphinine (tmbp) in the redox series fac-[Mn(Br)(CO)3(tmbp)], [Mn(CO)3(tmbp)]2, and [Mn(CO)3(tmbp)](-): crystallographic, spectroelectrochemical, and DFT computational study - Hartl, Frantisek; Mahabiersing, Taasje; Le Floch, Pascal; Mathey, Francois; Ricard, Louis; Rosa, Patrick; Zális, Stanislav (Inorganic chemistry, 2003)
Stepwise electrochemical reduction of the complex fac-[Mn(Br)(CO)(3)(tmbp)] (tmbp = 4,4',5,5'-tetramethyl-2,2'-biphosphinine) produces the dimer [Mn(CO)(3)(tmbp)](2) and the five-coordinate anion [Mn(CO)(3)(tmbp)](-). All three members of the redox series have been characterized by single-crystal X-ray diffraction. The crystallographic data provide valuable insight into the localization of the added electrons on the (carbonyl)manganese and tmbp centers. In particular, the formulation of the two-electron-reduced anion as [Mn(0)(CO)(3)(tmbp(-))](-) also agrees with the analysis of its IR nu(CO) wavenumbers and with the results of density functional theoretical (DFT) MO calculations on this compound. The strongly delocalized pi-bonding in the anion stabilizes its five-coordinate geometry and results in the appearance of several mixed Mn-to-tmbp charge-transfer/IL(tmbp) transitions in the near-UV-vis spectral region. A thorough voltammetric and UV-vis/IR spectroelectrochemical study of the reduction path provided evidence for a direct formation of [Mn(CO)(3)(tmbp)](-) via a two-electron ECE mechanism involving the [Mn(CO)(3)(tmbp)](*) radical transient. At ambient temperature [Mn(CO)(3)(tmbp)](-) reacts rapidly with nonreduced fac-[Mn(Br)(CO)(3)(tmbp)] to produce [Mn(CO)(3)(tmbp)](2). Comparison with the analogous 2,2'-bipyridine complexes has revealed striking similarity in the bonding properties and reactivity, despite the stronger pi-acceptor character of the tmbp ligand.